Instrumentation-free semiquantitative immunoanalysis using a specially patterned lateral flow assay device - Lee, Kyung Won; Yu, Ye Chan; Chun, Hyeong Jin; Jang, Yo Han; Han, Yong Duk; Yoon, Hyun C. (Biosensors, 2020)
In traditional colorimetric lateral flow immunoassay (LFI) using gold nanoparticles (AuNPs) as a probe, additional optical transducers are required to quantify the signal intensity of the test line because it presents as a single red-colored line. In order to eliminate external equipment, the LFI signal should be quantifiable by the naked eye without the involvement of optical instruments. Given this objective, the single line test zone of conventional LFI was converted to several spots that formed herringbone patterns. When the sandwich immunoassay was performed on a newly developed semi-quantitative (SQ)-LFI system using AuNPs as an optical probe, the spots were colorized and the number of colored spots increased proportionally with the analyte concentration. By counting the number of colored spots, the analyte concentration can be easily estimated with the naked eye. To demonstrate the applicability of the SQ-LFI system in practical immunoanalysis, microalbumin, which is a diagnostic marker for renal failure, was analyzed using microalbumin-spiked artificial urine samples. Using the SQ-LFI system, the calibration results for artificial urine-based microalbumin were studied, ranging from 0 to 500 µg/mL, covering the required clinical detection range, and the limit of detection (LOD) value was calculated to be 15.5 µg/mL. Thus, the SQ-LFI system provides an avenue for the realization of an efficient quantification diagnostic device in resource-limited conditions.
Keywords: Analyte concentration; Artificial urines; Immunoanalysis; Immunoassay system; Instrument-free quantitative analyse; Lateral flow immunoassay; Lateral-flow assays; Microalbuminuria; Naked-eye; Renal failure; Gold; Humans; Immunoassay; Limit of Detection; Metal Nanoparticles; Instrument-free quantitative analysis; Lateral flow immunoassay; Microalbuminuria; Renal failure